STRATEGI KOMUNIKASI PEMASARAN TERPADU NATURE CAKES DALAM MEMBANGUN BRAND AWARENESS HEALTHY CAKES - Purwita, Gst Ayu Mika Indah; Pascarani, Ni Nyoman Dewi; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2019)
ABSTRACT Nature Cakes is a MSME engaged in the business of Food, especially Cakes. Nature Cakes innovates by developing new cakes, so that new cakes are created besides tasty, also healthy for the body, in accordance with the jargon carried by "the real healty cakes". The purpose of the research is to find out the integrated marketing communication strategy undertaken by Nature Cakes in building a brand awareness of healthy cakes. The approach used in the study is a descriptive qualitative approach with the post-positivism paradigm. The researcher determined the informant by using purposive sampling. Data obtained through direct observation interviews and documentation studies. analytical techniques used in research through several stages, namely data reduction, data presentation, and conclusion. The results of the study show that Nature Cakes uses the Integrated Importance Communication Strategy in building Awarenes healthy cakes brand. Keyword: UMKM, IMC, Nature Cakes, Brand Awareness